Oxidative stress and reactive oxygen species in otorhinolaryngological diseases: insights from pathophysiology to targeted antioxidant therapies - Linghui Meng; Shengyang Liu; Jinfeng Luo; Yanyi Tu; Tao Li; Ping Li; Jinzhuang Yu; Li Shi (Redox Report)
Oxidative stress, characterized by an imbalance between excessive reactive oxygen species (ROS) production and impaired antioxidant defenses, is closely linked to the pathogenesis of various otorhinolaryngological disorders. Mitochondria, as the primary site of cellular energy production, play a crucial role in modulating oxidative stress. Mitochondrial dysfunction exacerbates ROS generation, leading to cellular damage and inflammatory responses. In otorhinolaryngological diseases, oxidative stress is strongly associated with conditions such as hearing loss, allergic rhinitis, and chronic sinusitis, where oxidative damage and tissue inflammation are key pathological features. Recent studies have highlighted the potential of antioxidant therapies to mitigate oxidative stress and restore homeostasis, offering promising avenues for alleviating symptoms in these diseases. However, despite the encouraging results from early-stage research, the clinical efficacy of antioxidant interventions remains to be fully established. This review provides an overview of the role of oxidative stress in otorhinolaryngological diseases and evaluates the therapeutic potential of antioxidant strategies.